MdZAT5 regulates drought tolerance via mediating accumulation of drought‐responsive miRNAs and mRNAs in apple. Issue 6 (4th November 2022) - Bao, Chana; Qin, Gege; Cao, Fuguo; He, Jieqiang; Shen, Xiaoxia; Chen, Pengxiang; Niu, Chundong; Zhang, Dehui; Ren, Tianyu; Zhi, Fang; Ma, Lei; Ma, Fengwang; et al.
Summary: Drought limits apple yield and fruit quality. However, the molecular mechanism of apple in response to drought is not well known. Here, we report a Cys2/His2 (C2H2)‐type zinc‐finger protein, MdZAT5, that positively regulates apple drought tolerance by regulating drought‐responsive RNAs and microRNAs (miRNAs). DNA affinity purification and sequencing and yeast‐one hybrid analysis identified the binding motifs of MdZAT5, T/ACACT/AC/A/G. Chromatin immunoprecipitation quantitative polymerase chain reaction (ChIP‐qPCR) and electrophoretic mobility shift assays (EMSAs) showed that MdZAT5 directly binds to the promoters of the drought‐responsive genes including MdRHA2a, MdLEA14, MdTPX1, and MdCAT3, and activates their expression under drought stress. MdZAT5 interacts with and directly targets HYPONASTIC LEAVES1 (MdHYL1). MdZAT5 may facilitate the interaction of MdHYL1 with pri‐miRNAs or MdDCL1 by activating MdHYL1 expression, thereby regulating the biogenesis of drought‐responsive miRNAs. Genetic dissection showed that MdHYL1 is essential for MdZAT5 ‐mediated drought tolerance and miRNA biogenesis. In addition, ChIP‐qPCR and EMSA revealed that MdZAT5 binds directly to the promoters of some MIR genes including Mdm‐miR171i and Mdm‐miR172c, and modulates their transcription. Taken together, our findings improve our understanding of the molecular mechanisms of drought response in apple and provide a candidate gene for the breeding of drought‐tolerant cultivars.